Profile and challenges of interdisciplinary physics - Mantegna, R. N. (Frontiers in Physics, 2024)
We discuss profile and challenges of interdisciplinary physics. We start discussing the current definition of physics. We therefore focus on the type of experimental settings observed in different branches of physics. We recall how the term predictability has changed over the last century and we comment on the effects of data deluge in science and society. Lastly we present a few examples profiles and challenges of interdisciplinary physics.